MEDIATION AS A MODEL FOR DISPUTE SETTLEMENT ON CONSTRUCTION WORK CONTRACT IN INDONESIA - Hendrik E. Purnomo (Global Legal Review, 2023)
As one of the essential elements in national development activities, activity of Construction Services needs to be based on statutory regulations which are clear, effective and adequate. This is important because in practice disputes often arise which involves Construction Services parties, especially disputes arising from Construction Work Contract. In Indonesia, Construction Disputes are mostly resolved through litigation or arbitration, which are considered less efficient in terms of business interests. Adjudicative decisions are considered less accommodating the business needs of the Construction Services’ parties because they often ended the relationship and potentially disrupted cooperation in the future. By using the judicial normative method, this Research intended to examine Mediation as a resolution mechanism of Construction Disputes with Construction Settlement Agreement as the output that provides a win-win solution for disputed parties based on good faith of each party. The legal materials used are laws and regulations, courts’ verdicts, journals and also law books. The result of this Research concluded that Mediation in Indonesia was still an alternative, so that it was only considered as a stage that needed to be passed before finally choosing a solution through arbitration or litigation. In developed countries, Mediation has become one of the options for resolving businesses disputes, including on the Construction Services area, which provides quite satisfactory results for the disputing parties, especially from the aspect of sustainability of business relationships in the future. This Research recommends the need for Mediators in Mediation to always have a neutral position in order to assist and escort the disputing parties to find agreement of settlement accordi12ng to their own will and ability, so that the Construction Settlement Agreement can be executed immediately. For this reason, Indonesia needs to carry out reformation related to Mediation, both in the form of regulations and institutions as well as the legal culture of the community of Construction Services.Keywords: Mediation, Construction Disputes, Win-Win Solution